2011
DOI: 10.1021/ja211444m
|View full text |Cite
|
Sign up to set email alerts
|

Total Synthesis of (−)-Fusarisetin A and Reassignment of the Absolute Configuration of Its Natural Counterpart

Abstract: The first total synthesis of (-)-fusarisetin A, the enantiomer of naturally occurring acinar morphogenesis inhibitor (+)-fusarisetin A, was accomplished in 13 steps, leading to the reassignment of the absolute configuration of the natural product. The synthesis featured a Lewis acid-promoted intramolecular Diels-Alder reaction, a Pd-catalyzed O→C allylic rearrangement, a chemoselective Wacker oxidation, and a Dieckmann condensation/hemiketalization cascade.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
45
0
3

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 75 publications
(52 citation statements)
references
References 27 publications
4
45
0
3
Order By: Relevance
“…Synthetic (−)-fusarisetin A was identical in all aspects with naturally occurring fusarisetin A ( 1 H-NMR, 13 C-NMR and HR-MS), except for the optical rotation (synthetic: [α] D 23 = −86.2 (c = 0.065 in MeOH); natural: [α] D 25 = +84.6 (c = 0.2 in MeOH) 13 , reported synthetic (−)- 1 : [α] D 27 = −88.0 (c = 0.15 in MeOH). 14 The structure of ent -C 5 - epi -1 was confirmed by comparison to the literature data. 14,16 …”
Section: Resultssupporting
confidence: 56%
See 2 more Smart Citations
“…Synthetic (−)-fusarisetin A was identical in all aspects with naturally occurring fusarisetin A ( 1 H-NMR, 13 C-NMR and HR-MS), except for the optical rotation (synthetic: [α] D 23 = −86.2 (c = 0.065 in MeOH); natural: [α] D 25 = +84.6 (c = 0.2 in MeOH) 13 , reported synthetic (−)- 1 : [α] D 27 = −88.0 (c = 0.15 in MeOH). 14 The structure of ent -C 5 - epi -1 was confirmed by comparison to the literature data. 14,16 …”
Section: Resultssupporting
confidence: 56%
“…37 Reduction of the alkoxylamine bond of ent -14 under Zn/AcOH conditions 38 liberated the C 5 -alcohol that underwent the desired hemiketalization, along with concomitant deprotection of the TBS group, to form a compound that was spectroscopically identified as the C 5 -epimer of (−)-fusarisetin A ( ent -C 5 -( epi -1 ). 14 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the moderate diastereoselectivity, this onepot radical cyclization/aminolysis reaction cascade 24 offers a concise way to build up the fusarisetin core structure. Subsequently, the C-5 hydroxy group of compound 4 was liberated under Zn/AcOH conditions 25 Treatment of the resulting C-5 alcohol under basic conditions (NaOMe) induced a one-pot Dieckmann condensation/ hemiacetaliza- tion 5,7 (construction of DE rings) ultimately producing fusarisetin A ( 1 ) in 42% overall yield. Importantly, the C 5 - epi - 4 could be also converted to fusarisetin A via a 3-step sequence that included: a) oxidative cleavage of the N-O bond with m CPBA 26 to form ketone 16 ; b) regioselective and stereoselective reduction of the C-5 ketone with NaBH 4 (d.r.= ca.…”
mentioning
confidence: 99%
“…The isolated sample of synthetic 1 was found to be identical in all aspects with naturally occurring fusarisetin A ( 1 H-NMR, 13 C-NMR and HR-MS), except for the optical rotation [synthetic: [α] D 23 = −86.2 (c = 0.065 in MeOH); natural: [α] D 25 = +84.6 (c = 0.2 in MeOH) 1 , reported synthetic (−)- 1 : [α] D 27 = −88.0 (c = 0.15 in MeOH) 7 ]. The chemical synthesis of 1 confirmed that the absolute stereochemistry of natural fusarisetin A is opposite to our synthetic 1 and provides support for its proposed biosynthesis.…”
mentioning
confidence: 99%